ce-time coded scheme for two-way relay system - Feng LI; Lei WANG; Zhi-gang CHEN (Tongxin xuebao)
In two-way relay system,focusing on the problem that using SSK transmission can not achieve the transmit diversity and has lower spectral efficiency,a diagonal space-time coded spatial modulation scheme called DSTC-SM scheme was proposed.In the DSTC-SM scheme,the source nodes transmit signals to the relay node by using the DSTC-SM codewords,and then the relay node equipped with one antenna amplifies the received signals and broadcasts them to the destination nodes.The proposed scheme uses the diagonal space-time codes as the core space-time block code (STBC) to construct the DSTC-SM codewords,and combines with SM technology to take advantage of the benefits of DSTC and SM.The antenna pairs activated in different codewords are moving cyclically along the total transmit antenna array.In addition,the rotation angles are further optimized to maximize the diversity and coding gains of the DSTC-SM codewords,so the proposed scheme can still obtain diversity gain even though only one transmit antenna is activated.Simulation results show that the proposed scheme outperforms the existing schemes.